2015
DOI: 10.1093/jisesa/iev005
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition Preference and Offspring Performance of Mechoris ursulus (Coleoptera: Attelabidae) in Cyclobalanopsis glaucoides (Fagales: Fagaceae) and Quercus franchetii (Fagales: Fagaceae) in Central Yunnan, China

Abstract: Mechoris ursulus (Roelofs) (Coleoptera: Attelabidae) is a pest weevil of Fagaceae oak trees in eastern Asia. The female has a distinct branch-cutting behavior in conjunction with oviposition in the acorns of its host plant. This study analyzed the factors influencing oviposition preference by carrying out continuous field surveys over the course of 2009–2010 and through laboratory rearing. The field survey showed that for both of the hosts, Cyclobalanopsis glaucoides Schottky (Fagales: Fagaceae) and Quercus fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
1
4
0
1
Order By: Relevance
“…(2003) and Wang et al . (2015) reported that M. ursulus progeny in big corns emerge as larger adults than those emerging from small corns. Here, we found that cradle size did not affect the weight of emerging adults in A. dimidiatus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2003) and Wang et al . (2015) reported that M. ursulus progeny in big corns emerge as larger adults than those emerging from small corns. Here, we found that cradle size did not affect the weight of emerging adults in A. dimidiatus .…”
Section: Discussionmentioning
confidence: 99%
“…2003; Wang et al . 2015). Females of Cycnotrachelus roelofsi (Coleoptera: Attelabidae) prefer larger leaves (Tokuda et al .…”
Section: Introductionmentioning
confidence: 99%
“…The females of the weevil family Attelabidae (Coleoptera: Curculionoidea) damage or destroy the host organs before and after oviposition, such as cutting buds, shoots, petioles, leaves, and fruit branches [ 16 , 17 , 18 ], leading to the destruction of the conducting tissue. These ovipositing behaviours consume vast amounts of time and energy, although the number of eggs laid is usually limited [ 19 , 20 ]. The motivation for this time-consuming and laborious oviposition behaviour of attelabid weevils includes (1) induction of decay (including fungal growth), which forms preprocessing food for the larvae; and (2) providing protection by leaf rolls or other plant organs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding drosophilid species, a preference for ovipositing in a given resource between several available is influenced by internal metabolic states and the type of food ingested (Jaenike, 1983; Sheeba et al, 1998), by genetic composition (Dahlgaard et al, 2001; Markow & O’Grady, 2008; Miller et al, 2011; Betti et al, 2014; Soto et al, 2015), as well as by external biotic and abiotic factors, including temperature, humidity, predators, competitors, and nutritional status of the host (Hougouto et al, 1982; Worthen, 1989; Markow & O’Grady, 2008; Miller et al, 2011; Soto et al, 2011, 2012; Kacsoh et al, 2015; Matavelli et al, 2015; Hamby et al, 2016; Karageorgi et al, 2017; Zerulla et al, 2017; Kidera & Takahashi, 2020; Winkler et al, 2020; Ulmer et al, 2021). Also, as immature stages of drosophilids cannot move large distances between resources (different fruits for instance), it is expected that females’ evaluation and selection of the resources where their progeny will develop is an important factor in relation to fitness (Taylor, 1987; Bernays & Chapman, 1994; Yang et al ., 2008; Soto et al, 2012; Markow, 2019) and invasion success (Atallah et al, 2014; Wang et al, 2015; Shragai et al, 2019; Kienzle et al, 2020).…”
Section: Introductionmentioning
confidence: 99%